ANALISIS PENDAPATAN PETANI PADI SAWAH DI DESA SIHEPENG KECAMATAN SIABU KABUPATEN MANDAILING NATAL PROVINSI SUMATERA UTARA - Endro Freddy; Roza Yulida; Evy Maharani (Indonesian Journal of Agricultural Economics, 2016)
Agricultural extension as part of the national life (especially farmers) and promote the general welfare is one of the keys to success for strengthening farmer groups. The purpose of this research were: 1) To analyze the cost of production of paddy rice farming in the village SihepengSiabu District Mandailing Natal Regency of North Sumatera Province. 2) To analyze the income of rice farmers in the village Sihepeng Siabu District Mandailing NatalRegency was conducted in the village Sihepeng Siabu District Mandailing Natal Regency began in May through July 2015. The method used in this study is a survey and sampling techniques disproportionately stratified Random Sampling. The sampling of 50% of the population, consisting of beginner classes as much as 54 (fifty-four) advanced classes as much as 9 (nine) farmers. The results showed the average total cost of production of 0.1-1 ha land area amounting to Rp 3,321,868 and the average total cost of production land area> 1 ha Rp 18,840,333 total net income received by farmers with land area 0,1-1 Rp 545 132 800 ha with an average income of Rp 8,016,659. Total net revenues received by farmers with land area of> 1 Ha Rp 638 586 400 with an average net income of Rp 42,572,427. Comparison of the results of the income of farmers with an area of 0.1-1 ha of rice field and> 1 ha much greater level of income of farmers in land area> 1 ha due to differences in the area of land owned by farmers. Results expected that the income of farmers in the village Sihepeng better to have a land area of 0.2 ha to be more efficient in the utilization of paddy fields in the village Sihepeng.